The prognostic value of the furosemide stress test in predicting delayed graft function following deceased donor kidney transplantation. (2nd January 2018) - McMahon, Blaithin A.; Koyner, Jay L.; Novick, Tessa; Menez, Steve; Moran, Robert A.; Lonze, Bonnie E.; Desai, Niraj; Alasfar, Sami; Borja, Marvin; Merritt, William T.; Ariyo, Promise; Chawla, Lakhmir S.; et al.
Abstract: Objectives and methods: The Furosemide Stress Test (FST) is a novel dynamic assessment of tubular function that has been shown in preliminary studies to predict patients who will progress to advanced stage acute kidney injury, including those who receive renal replacement therapy (RRT). The aim of this study is to investigate if the urinary response to a single intraoperative dose of intravenous furosemide predicts delayed graft function (DGF) in patients undergoing deceased donor kidney transplant. Results: On an adjusted multiple logistic regression, a single 100 mg dose of intraoperative furosemide after the anastomosis of the renal vessels (FST) predicted the need for RRT at 2 and 6 h post kidney transplantation (KT). Recipient urinary output was measured at 2 and 6 h post furosemide administration. In receiver-operating characteristic (ROC) analysis, the FST predicted DGF with an area-under-the curve of 0.85 at an optimal urinary output cut-off of <600 mls at 6 h with a sensitivity of and a specificity of 83% and 74%, respectively. Conclusions: The FST is a predictor of DGF post kidney transplant and has the potential to identify patients requiring RRT early after KT.